Cognitive-behavioral Guidance Program To Reduce Examination Anxiety At The End Of Primary Education - Bassi Baha; Djeloul Ahmed (University of Eloued جامعة الوادي, 2024)
Abstract: The study aimed to propose a cognitive-behavioral guidance program to reduce examination anxiety at the end of primary education at Tijini El Taher Elementary School (El oued) during the academic season 2022-2023. This guidance program seeks to alleviate examination anxiety, considering it as a variable that poses a real problem for students that needs adjustment. This is achieved through the utilization of cognitivebehavioral guidance methods and techniques. Using an experimental design with two independent groups (experimental and control), the study involved a sample of 24 students, divided into two groups: an experimental group of 12 students and a control group of 12 students from the fifth grade. The proposed guidance program was applied to the experimental group in this study. After exposing the experimental group to a cognitive-behavioral guidance program aimed at reducing examination anxiety at the end of primary education, the program was conducted over twelve sessions. The control group continued their studies in a regular manner without any intervention. Both groups underwent pre-test and post-test measurements using an examination anxiety scale. The results revealed statistically significant differences between the two groups in favor of the experimental group. The scores of the experimental group in reducing examination anxiety were higher compared to the control group. Furthermore, females showed greater improvement than males after exposure to the cognitive-behavioral guidance program. Thus, the proposed guidance program proved to be effective in reducing examination anxiety at the end of primary education.
Keywords: Guidance Program; Cognitive-Behavioral; Examination Anxiety; Achievement Assessment; Primary Education Stage